Achalasia Combined with Idiopathic Gastroparesis Treated with Peroral Endoscopic Myotomy and Gastric Peroral Endoscopic Myotomy in a Single Procedure - Wang, Yating; Zhang, Chunxi; Zhao, Dongqiang (Turkish Journal of Gastroenterology, 2023)
Cite this article as: Wang Y, Zhang C, Zhao D. Achalasia combined with idiopathic gastroparesis treated with peroral endoscopic myotomy and gastric peroral endoscopic myotomy in a single procedure. Turk J Gastroenterol. 2023;34(9):982-983.